Female sexual dysfunction among contraceptive user in Malaysia - Ismail, Adibah Hanim; Md Salleh, Hafizah; Ching, Siew Mooi (Madridge Publishers, 2017)
Background: Women in reproductive age are at risk of getting female sexual dysfunction (FSD). Contraception has been recognized as one of the causes of FSD. This study aims to determine the prevalence of FSD and types of FSD among contraceptive user. Methods: This is a cross-sectional study involving 262 women who were on contraception in eleven primary care clinics in Malaysia. Malay version of Female Sexual Function Index (MVFSFI) was used in this study. Results: The prevalence of FSD among contraceptive user in Malaysia was 9.5% (n=25). The highest types of female sexual dysfunction in this study were sexual dissatisfaction (29.8%, n=78) and sexual desire disorder (29.4%, n=77). Majority of the participants were Malay (83.6%). Of twenty-five women with FSD, one-third of them was Indian ethnic. Most of the women (11.2%) with FSD had received education up to secondary school and non- employed (11.6%). Twenty-two (9.9%) women with FSD were practising hormonal contraception and most of them were dissatisfied with their marital relationship (35.7%, n=5). Conclusions: The result indicates that one in ten contraceptive users had FSD. The highest percentage of female sexual dysfunction domain was sexual dissatisfaction and sexual desire disorder. Hormonal contraception was the most common method used among women with FSD. Further research is needed to determine the associated factor of female sexual dysfunction among women using contraception.